Negosiasi Islam dan Budaya Lokal pada Terjemahan Novel â€œKisah Seribu Satu Malamâ€: Sebuah Kajian Parateks - muhammad rokib; Moh Mudzakkir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
Alf Laylah wa Laylah novel (tales) translated as â€œThe Arabian Nightsâ€ and â€œKisah Seribu Satu Malamâ€ is a popular literature in the world. Through the Antoine Galland translation in 1704 entitled Les mille et une nuits, the novel had translated as The Arabian Night and widespread to all over the world. In Indonesia, the Arabian Nights received great reception from the society. One of the empirical evidences from the reception is a Mizan publisher translation which was reached to nineteenth edition. Mizan has translated it by â€œKisah Seribu Satu Malamâ€ from the English edition. In 2004, the first volume had nineteen edition, while second has fifteen. These frequences of edition showed the Indonesian people interest to the novel. Through the paratext approach which scrutinizes text from the cover of novel include images, codes, symbols, text and combinated design, this paper argues that translated edition of Kisah Seribu Satu Malam has reflected local readersâ€™ reception considering local culture. Within various covers design, there has been similar message on peaceful and humorous symbol of Indonesian Islam.